2010
DOI: 10.7322/jhgd.19958
|View full text |Cite
|
Sign up to set email alerts
|

Tendência secular de crescimento em pré-escolares, Brasil

Abstract: INTRODUÇÃO: a análise da distribuição temporal de eventos do processo saúde-doença é uma das estratégias de investigação mais antigas e valiosas para a epidemiologia e para a saúde pública. OBJETIVO: analisar a evolução do perfil antropométrico de pré-escolares, que frequentavam creches municipais da cidade de Taubaté em 1997 e 2007. MÉTODO: foram analisadas variáveis do banco de dados de 2 estudos transversais: um realizado em 1997, com 755 crianças, e outro de 2007, com 1448 crianças. Os dados analisados for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 18 publications
0
2
0
1
Order By: Relevance
“…The relevance of these results is that stature growth, especially in developing countries, may represent an advance in the health conditions of children and young people, since it is one of the indicators of quality of life in a country. This secular trend of growth has been observed in some regions of Brazil since the end of the 1990s, and can be interpreted from the perspective of improving the social determinants of health and can also integrate the process of nutritional transition, including outside the major metropolitan areas 20 .…”
Section: Discussionmentioning
confidence: 80%
“…The relevance of these results is that stature growth, especially in developing countries, may represent an advance in the health conditions of children and young people, since it is one of the indicators of quality of life in a country. This secular trend of growth has been observed in some regions of Brazil since the end of the 1990s, and can be interpreted from the perspective of improving the social determinants of health and can also integrate the process of nutritional transition, including outside the major metropolitan areas 20 .…”
Section: Discussionmentioning
confidence: 80%
“…1 In this sense, overweight and obesity, described as having an increasing prevalence in the population and now also affecting very young children, even in families of lower socioeconomic status, in several studies, have been linked to birth weight. [2][3][4][5] Research has also shown that low birth weight is associated with the development of chronic noncommunicable diseases in adulthood, especially when due to intrauterine growth restriction (IUGR) and excess weight in childhood. [6][7][8][9] According to Martins and Carvalho, 10 among the various factors that have been linked to overweight and obesity in childhood, birth weight appears all too often.…”
Section: Introductionmentioning
confidence: 99%
“…Fatores ambientais como condições socioeconômicas, condições sanitárias, controle de doenças infecciosas, renda mínima, nível de educação, industrialização e urbanização são fatores importantes, que podem bloquear a expressão plena do potencial genético individual (Nascimento et al, 2010). Nos últimos anos, tem sido verificado um aumento da prevalência de excesso de peso, simultaneamente à redução dos quadros de desnutrição.…”
Section: Introductionunclassified